Towards a multidimensional root trait framework: a tree root review - Weemstra, Monique; Mommer, Liesje; Visser, Eric J. W.; Ruijven, Jasper; Kuyper, Thomas W.; Mohren, Godefridus M. J.; Sterck, Frank J. (The New phytologist, 2016)
The search for a root economics spectrum (RES) has been sparked by recent interest in trait-based plant ecology. By analogy with the one-dimensional leaf economics spectrum (LES), fine-root traits are hypothesised to match leaf traits which are coordinated along one axis from resource acquisitive to conservative traits. However, our literature review and meta-level analysis reveal no consistent evidence of an RES mirroring an LES. Instead the RES appears to be multidimensional. We discuss three fundamental differences contributing to the discrepancy between these spectra. First, root traits are simultaneously constrained by various environmental drivers not necessarily related to resource uptake. Second, above- and belowground traits cannot be considered analogues, because they function differently and might not be related to resource uptake in a similar manner. Third, mycorrhizal interactions may offset selection for an RES. Understanding and explaining the belowground mechanisms and trade-offs that drive variation in root traits, resource acquisition and plant performance across species, thus requires a fundamentally different approach than applied aboveground. We therefore call for studies that can functionally incorporate the root traits involved in resource uptake, the complex soil environment and the various soil resource uptake mechanisms – particularly the mycorrhizal pathway – in a multidimensional root trait framework.